Pesantren Education in Shaping Santri Character in the Digital Age at Roudlotus Sholihin Kedali Pucuk Islamic Boarding School - Yulia Nadzifah; Siti Lathifatus Sun'iyah; Nayla Zulfia; Achmad Fatoni (AJER: Advanced Journal of Education and Religion, 2024)
Islamic boarding schools have an important role in shaping the character of good and tolerant students. Even though they still maintain tradition, pesantren also have to face challenges in the era of changing times. This requires Islamic boarding schools to be able to harmonize with the new, better culture, while still holding fast to the values and teachings of the previous scholars. Lamongan (2) To find out the method of the Roudlotus Sholihin Islamic boarding school in shaping the character of students in the digital era (3) To find out the inhibiting and driving factors of the role of Islamic boarding schools in shaping the character of students in the digital era. This type of research is field research with a qualitative approach. The results of the research are as follows: in the formation of the character of the students, namely through teaching and learning activities, guidance on how to pray, extracurricular activities and admonishing the students. This is accomplished with Islamic boarding schools which are education providers that are able to teach students not only theory but also practice it directly. In shaping the character of the students of the Roudlotus Sholihin Islamic Boarding School, the method of lecturing, exemplary, habituation and giving advice and punishment is used to train the moral and mental students of the students. Then the supporting factor in carrying out its role is the growing sense of enthusiasm of the students to study and is supported by the boarding school environment which has a positive influence on the students. On the other hand, the inhibiting factor was that the students found it difficult to manage their time because of the tightness of the boarding school activities so that the students became bored, lazy and sleepy during learning activities